The ICP0 Protein of Herpes Simplex Virus 1 (HSV-1) Downregulates Major Autophagy Adaptor Proteins Sequestosome 1 and Optineurin during the Early Stages of HSV-1 Infection - Waisner, Hope (J Virol, 2019)
Herpes simplex virus 1 (HSV-1) infects mucosal epithelial cells and establishes lifelong infections in sensory neurons. Following reactivation, the virus is transferred anterograde to the initial site of infection or to sites innervated by infected neurons, causing vesicular lesions. Upon immunosuppression, frequent HSV-1 reactivation can cause severe diseases, such as blindness and encephalitis. Autophagy is a process whereby cell components are recycled, but it also serves as a defense mechanism against pathogens. HSV-1 is known to combat autophagy through the functions of the γ(1)34.5 protein, which prevents formation of the autophagophore by binding to Beclin 1, a key factor involved in the elongation of the isolation membrane, and by redirecting the protein phosphatase 1α (PP1α) to dephosphorylate the translation initiation factor 2α (eIF2α) to prevent host translational shutoff. Other viral proteins that counteract innate immunity negatively impact autophagy. Here, we present a novel strategy of HSV-1 to evade the host through the downregulation of the autophagy adaptor protein sequestosome (p62/SQSTM1) and of the mitophagy adaptor optineurin (OPTN). This down-modulation occurs during the early steps of the infection. We also found that infected cell protein 0 (ICP0) of the virus mediates the down-modulation of the two autophagy adaptors in a mechanism independent of its E3 ubiquitin ligase activity. Cells depleted of either p62 or OPTN were able to mount greater antiviral responses, whereas cells expressing exogenous p62 displayed decreased virus yields. We conclude that downregulation of p62/SQSTM1 and OPTN is a viral strategy to counteract the host. IMPORTANCE Autophagy is a homeostatic mechanism of cells to recycle components, as well as a defense mechanism to get rid of pathogens. Strategies that HSV-1 has developed to counteract autophagy have been described and involve inhibition of autophagosome formation or indirect mechanisms. Here, we present a novel mechanism that involves downregulation of two major autophagy adaptor proteins, sequestosome 1 (p62/SQSTM1) and optineurin (OPTN). These findings generate the question of why the virus targets two major autophagy adaptors if it has mechanisms to block autophagosome formation. P62/SQSTM1 and OPTN proteins have pleiotropic functions, including regulation of innate immunity, inflammation, protein sorting, and chromatin remodeling. The decrease in virus yields in the presence of exogenous p62/SQSTM1 suggests that these adaptors have an antiviral function. Thus, HSV-1 may have developed multiple strategies to incapacitate autophagy to ensure replication. Alternatively, the virus may target another antiviral function of these proteins.